Büro Berlin : Ein Produktionsbegriff - Kummer, Raimund; Pitz, Hermann; Rahmann, Fritz; Künstlerhaus Bethanien, Berlin (Berlin : Künstlerhaus Bethanien, 1986)
Aalders, Franklin ; Arpagaus, Elisabeth ; Bachhofer, Jörg ; Bentrup, Jochen ; Bernhardt, Uli ; Bertoncini, Mario ; Bezemer, Nick ; Filer, Ferry ; Binder, Konstanze ; Bode, Wolfgang ; Bodeving, Leonie ; van der Borght, Christian ; Brixius, Gerd ; Buschmann, Ingrid ; Butzmann, Frieder ; Chebbi, Messaoud ; Chopper ; Claus, Richard ; Cragg, Tony ; etc.
Büro Berlin : Ein Produktionsbegriff, Künstlerhaus Bethanien, Berlin 1986
boek